Design, simulation, and experimental investigation on a novel multi-mode piezoelectric acoustofluidic device for ICF target manipulation. (4th February 2022) - Wang, Xin; Wang, Liang; Feng, Haoren; Jin, Jiamei; Yin, Qiang
Abstract: The Inertial Confinement Fusion (ICF) targets are hollow glass microspheres with strong viscosity, easy agglomeration, small diameter, and fragile structure. The size and morphology of the ICF target are crucial to the success of ICF experiment. To obtain qualified targets, the manual detection method and automatic detection systems are mainly employed. However, hard contact existed between the targets and the manipulation platform in both methods, which may cause target damage. To solve this issue, a novel multi-mode piezoelectric acoustofluidic manipulation device is proposed to achieve the non-contact manipulation of sub-millimeter size ICF targets during detection process. The proposed device mainly consists of a disk-shaped container and a four-transducer array. Standing and traveling vibration modes can be separately stimulated in the container when the four-transducer array is excited with a specific signal sequence. The modal simulation is first conducted to determine the dimensional parameters and required vibration modes. Furthermore, the acoustic streaming field simulation is used to verify the effectiveness of the modal simulation and interpret the manipulation mechanism. Then, the correctness of the simulation results is demonstrated through the experiments. In the experiments, the influences of the driving frequency, target diameter, and excitation voltage on the linear manipulation are investigated through an image recognition program, respectively. The target can be linearly manipulated, and has a maximum speed of 19.10 mm s −1 at 21.5 kHz. Furthermore, with the increase of the target diameter and excitation voltage, the speed of the target increases. Finally, the rotational manipulation of the targets are conducted, and the target can effectively rotate in the container at the driving frequency of 24.6 kHz. The proposed acoustofluidic manipulation device holds the merits of simple structure, low-frequency, multi-mode, and large particle manipulation ability, which may provide technical support for the detection and filter of ICF targets.